2019
DOI: 10.1111/1475-6773.13251
|View full text |Cite
|
Sign up to set email alerts
|

Eight‐year post‐trial follow‐up of health care and long‐term care costs of tele‐based health coaching

Abstract: Objective To evaluate the long‐term effect of telephone health coaching on health care and long‐term care (LTC) costs in type 2 diabetes (T2D) and coronary artery disease (CAD) patients. Data Sources/Study Setting Randomized controlled trial (RCT) data were linked to Finnish national health and social care registries and electronic health records (EHR). Post‐trial eight‐year economic evaluation was conducted. Study Design A total of 1,535 patients (≥45 years) were randomized to the intervention (n = 1034) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Only one article did not report a result as compared to the control group because it was a posttrial analysis and it did not address the control group. [28,32,35,38,40,41,43,46,[48][49][50][53][54][55][58][59][60]64] Telemedicine improved results compared to control 9 ( 14) [27,30,33,34,39,45,51,56,62] No statistically significant difference 7 (11) [24,25,43,47,49,50,63] Improved patient satisfaction 6 (9) [36,49,60,62,64,67] Improved health behaviors 6 (9) [22,38,40,41,49,67] Improved compliance/adherence 5 (8) [28,…”
Section: Comparisons To a Control Groupmentioning
confidence: 99%
“…Only one article did not report a result as compared to the control group because it was a posttrial analysis and it did not address the control group. [28,32,35,38,40,41,43,46,[48][49][50][53][54][55][58][59][60]64] Telemedicine improved results compared to control 9 ( 14) [27,30,33,34,39,45,51,56,62] No statistically significant difference 7 (11) [24,25,43,47,49,50,63] Improved patient satisfaction 6 (9) [36,49,60,62,64,67] Improved health behaviors 6 (9) [22,38,40,41,49,67] Improved compliance/adherence 5 (8) [28,…”
Section: Comparisons To a Control Groupmentioning
confidence: 99%
“…It allowed us to make some observations of reduced cardiovascular events among those who participated to the study. In our previous TERVA -trial reporting [ 19 ], we found that the 8-year total social and health care costs were lower in intervention group; in ITT -analysis 3% lower (approx. €1200/patient/8-year) and in PP-analysis 14% lower (approx.…”
Section: Discussionmentioning
confidence: 79%
“…In long-term follow-up, over 8 years, we found that the total social and health care costs were lower in the intervention group. During the first two years costs were higher in THC -group, but after that the costs were lower to the end of the follow-up period [ 19 ]. While behavioural changes, such as health coaches’ learning of coaching skills and patients’ lifestyle changes, can take 1–3 years to actualize, the effectiveness of THC -intervention may be delayed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The costs for each diagnosis were calculated using the computational standard cost [ 46 , 47 ] using patient grouping methods and standard unit costs calculated from national-level cost accounting projects. Hospitalizations and hospital outpatient visits were grouped using the Nordic Diagnosis-Related Groups grouper.…”
Section: Methodsmentioning
confidence: 99%